Mindfulness in Adolescents: How is the Mindfulness of IJSO Participants? - Yuni Nur Rohman; Anne Hafina Adiwinata; Nadia Aulia Nadhirah; Ipah Saripah; Yuni Nur Rohman; Anne Hafina Adiwinata; Nadia Aulia Nadhirah (Universitas Negeri Malang, 2025)
Mindfulness is a necessary psychological state for adolescents. Mindfulness is essential in improving mental health and psychological well-being and can help adolescents optimize their learning process or cognitive and academic performance as students. The study aimed to obtain empirical data on mindfulness tendencies in adolescent candidates for International Junior Science Olympiad (IJSO) participants. The research method used is a mixed method with a convergent parallel design. The research sample was 12 adolescents who were candidates for the IJSO or International Junior Science Olympiad in 2022. The study results showed that the tendency of mindfulness in adolescent IJSO candidate participants was mainly in the high mindfulness category, and when reviewed based on the analysis of mindfulness aspects, behavioral indicators or characteristics of mindfulness tendencies in each IJSO candidate participant were quite diverse.